2014
DOI: 10.1002/14651858.cd000009.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and related interventions for smoking cessation

Abstract: Background Acupuncture and related techniques are promoted as a treatment for smoking cessation in the belief that they may reduce nicotine withdrawal symptoms. Objectives The objectives of this review are to determine the e ectiveness of acupuncture and the related interventions of acupressure, laser therapy and electrostimulation in smoking cessation, in comparison with no intervention, sham treatment, or other interventions. Search methods We searched the Cochrane Tobacco Addiction Group Specialized Registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 59 publications
7
77
0
6
Order By: Relevance
“…Acupuncture and acupressure (a similar treatment that uses stimulation of specific points in the body without the use of needles) have been evaluated as potential CAM treatments for smoking cessation (e.g., White, Rampes, Liu, Stead, & Campbell, 2014;White & Taylor, 2014) and depression (e.g., Stub, Alraek, & Liu, 2011). In particular, some have suggested that these treatments may be effective for smoking cessation by reducing nicotine withdrawal symptoms; however, these studies were uncontrolled .…”
Section: Acupuncture and Acupressurementioning
confidence: 99%
“…Acupuncture and acupressure (a similar treatment that uses stimulation of specific points in the body without the use of needles) have been evaluated as potential CAM treatments for smoking cessation (e.g., White, Rampes, Liu, Stead, & Campbell, 2014;White & Taylor, 2014) and depression (e.g., Stub, Alraek, & Liu, 2011). In particular, some have suggested that these treatments may be effective for smoking cessation by reducing nicotine withdrawal symptoms; however, these studies were uncontrolled .…”
Section: Acupuncture and Acupressurementioning
confidence: 99%
“…Although proposed to act by weakening the desire to smoke and strengthening the will to stop, and widely promoted as methods to aid smoking cessation, the effects described in uncontrolled studies have been notoriously difficult to confirm in randomized controlled trials [37]. Recent rigorous evidence-based reviews suggest there is no clear evidence of a benefit for either acupuncture or hypnotherapy [38,39]. Acupuncture was less effective than nicotine replacement therapy, and hypnotherapy did not have a greater effect than any other intervention or no therapy.…”
Section: The Professional's Individual Rolementioning
confidence: 99%
“…30 % [6]; Willenskraft allein: maximal 5 % [9]). Zugleich wurde die in einer Cochrane-Analyse [24] belegte Effektivität einer hausärztlichen Beratung von den Studierenden deutlich geringer eingeschätzt als die Effektivität der Akupunktur -für letztere wurde bislang kein Effektivitäts-nachweis erbracht [30]. Die Effektivitäts-Einschätzungen für Methoden zur Behandlung der Alkoholabhängigkeit waren etwas realistischer; so erkannten die Studierenden den Wert einer Entzugsbehandlung mit anschließender Entwöhnungstherapie sowie die moderate Effektivität von Selbsthilfegruppen [5], stationärem Entzug [16] und hausärztlicher Beratung [11] als alleinige Methoden zur Abstinenzaufrechterhaltung.…”
Section: Zusammenfassung ▼unclassified